2016
DOI: 10.1590/1807-1929/agriambi.v20n11p965-971
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance of cowpea-radish intercropping under different amounts of rooster tree biomass incorporated into the soil

Abstract: Intercropping systems of cowpea with radish are beginning to be deployed in the semiarid region of Rio Grande do Norte state. The great challenge is to know whether or not there is productive efficiency in these systems when fertilized with organic matter produced by spontaneous species from the ‘Caatinga’ biome. Thus, the aim of this study was to evaluate the productive performance of cowpea-radish intercropping systems under different amounts of rooster tree biomass incorporated into the soil. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
3
16
1
Order By: Relevance
“…The results found for the number of pods per m², number of grains per pod, yield of green grains and dry matter of grains, equal to 133.19, 8.27, 2.09 and 0.63 t ha -1 at the highest amount of hairy woodrose (55 t ha -1 ) incorporated to the soil, differed from those found by Pereira et al (2016), who analyzed the productive performance of the intercropping of green cowpea and radish under different amounts of 'flor-de-seda' (Calotropis procera) biomass incorporated to the soil, and obtained values of 159.6, 8.5, 3.60 and 1.30 t ha -1 , respectively.…”
Section: Number Of Pods M -2contrasting
confidence: 74%
“…The results found for the number of pods per m², number of grains per pod, yield of green grains and dry matter of grains, equal to 133.19, 8.27, 2.09 and 0.63 t ha -1 at the highest amount of hairy woodrose (55 t ha -1 ) incorporated to the soil, differed from those found by Pereira et al (2016), who analyzed the productive performance of the intercropping of green cowpea and radish under different amounts of 'flor-de-seda' (Calotropis procera) biomass incorporated to the soil, and obtained values of 159.6, 8.5, 3.60 and 1.30 t ha -1 , respectively.…”
Section: Number Of Pods M -2contrasting
confidence: 74%
“…Further, the number of green grains per pod increased with increase in the amount of roostertree biomass with the highest value of 6.88 grains per pod with 65 t ha -1 of roostertree biomass ( Fig 3B). These results are in agreement with those reported by Pereira et al (2016). They studied the effects of different amounts of roostertree biomass on the performance of a radish-cowpea intercropping system.…”
Section: Effects Of Treatments On the Agronomic Performance Of Cowpeasupporting
confidence: 92%
“…The green pod increased with the increase in the amount of roostertree biomass with the highest value of 2.08 t ha -1 with 65 t ha -1 of roostertree biomass ( Fig 4C). Pereira et al (2016) also observed an increase in the green pod with increase in the amount of roostertree biomass incorporated into the soil in a radish-cowpea intercropping system. These results suggest that roostertree efficiently supplies essential nutrients for the development and growth of cowpea (Batista et al, 2016a).…”
Section: Effects Of Treatments On the Agronomic Performance Of Cowpeamentioning
confidence: 69%
“…Silva and Neves (2011) found an HGW for the cultivars BRS Marataoã (15 g) and BRS Paraguaçu (16.7 g) similar to that considered as standard, and lower than the weight obtained in this study. However, these values are like those found by Pereira et al (2016), but lower than those seen by Souza et al (2016), who for the cultivar Setentão obtained a mean value for hundred-grain weight of 26.7g.…”
Section: Production Componentssupporting
confidence: 61%
“…In Brazil, cultivation of the cowpea occurs in the North and Northeast Regions, and comprises one of the main socioeconomic alternatives, both in the supply of food and the generation of employment and income; no longer a mere subsistence crop, it has assumed a certain technological standard through the use of fertilisers and agricultural correctives, and through mechanisation, technifying the harvesting process, considered the main bottleneck in the production system (Freire Filho et al, 2005;Pereira et al, 2016;Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%